In vivo three-dimensional imaging of human corneal nerves using Fourier-domain optical coherence tomography - Shin, Jun Geun; Hwang, Ho Sik; Eom, Tae Joong; Lee, Byeong Ha (Journal of biomedical optics, 2017)
We have employed Fourier-domain optical coherence tomography (FD-OCT) to achieve corneal nerve imaging, which could be useful in surgical planning and refractive surgery. Because the three-dimensional (3-D) images of the corneal nerves were acquired in vivo, unintentional movement of the subject during the measurement led to imaging artifacts. These artifacts were compensated for with a series of signal processing techniques, namely realigning A-scan images to flatten the boundary and cross-correlating adjacent B-scan images. To overcome the undesirably large signal from scattering at the corneal surface and iris, volume rendering and maximum intensity projections were performed with only the data taken in the stromal region of the cornea, which is located between 200 and 500  μm from the corneal surface. The 3-D volume imaging of a 10×10  mm2 area took 9.8 s, which is slightly shorter than the normal tear breakup time. This allowed us to image the branched and threadlike corneal nerve bundles within the human eye. The experimental results show that FD-OCT systems have the potential to be useful in clinical investigations of corneal nerves and by minimizing nerve injury during clinical or surgical procedures.